Digitalization and Its Impact on Accounting Standard-Setting: A Systematic Review - Dea Syakiroh Maghfirotun Nisa' (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
Purpose: This study aims to explain why and how digitalization influences the global accounting standard-setting process, particularly as emerging technologies introduce complexities that are not fully accommodated by existing regulations. Method: This research employs a Systematic Literature Review (SLR) using articles published between 2019–2025 obtained from Google Scholar, JSTOR, and Scopus. The selection process followed the PRISMA framework to identify and screen relevant studies related to digitalization and accounting standards. Results: The findings indicate that technologies such as blockchain, artificial intelligence, cloud computing, and XBRL have significantly transformed accounting recording, reporting, and auditing practices. However, current accounting standards remain limited in addressing key issues, including decentralized data validation, the reliability of AI-based decision models, digital data security, and the recognition of digital assets. Implications: These results imply that accounting standard-setting institutions, including the IASB, FASB, and IAI, need to formulate adaptive and forward-looking regulations to ensure alignment between technological advancements and fundamental accounting principles. Novelty: The novelty of this study lies in its integrated analysis that connects technological disruptions with existing regulatory gaps, providing structured recommendations for the future development of accounting standards.